Al-Qur'an Learning Models in Global Studies: Traditional and Modern Approaches - Zainuri, Habib; Mahmud, Muchammad Eka; Achmad Ruslan Afendi (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
however, in the contemporary global context it faces serious challenges due to digitalization, globalization, and increasing cultural diversity. While traditional learning models emphasize sanad, talaqqi, and spiritual discipline, modern approaches increasingly adopt digital platforms and blended learning. This study aims to analyze and synthesize the development of Qur’anic learning models from a global perspective by examining the dialectical relationship between traditional and modern approaches in Eastern and Western contexts. This research employs a qualitative document-based method using narrative and comparative analysis of international journal articles, academic books, and research reports published between 2015 and 2025. The data were analyzed thematically through coding, categorization, and critical synthesis. The findings indicate that traditional models such as Baghdadiyah, Iqro’, Qira’ati, and talaqqi-musyafahah remain essential in preserving the authenticity of recitation and spiritual depth, while digital and hybrid models enhance accessibility, flexibility, and learner engagement. These findings confirm that the sustainability of Qur’anic education in the global era depends on the development of an integrative–hybrid model that balances spiritual continuity and pedagogical innovation.